1996
DOI: 10.1089/jir.1996.16.813
|View full text |Cite
|
Sign up to set email alerts
|

Structural Requirements for Agonist Activity of a Murine Interferon-γ Peptide

Abstract: We have demonstrated previously that murine interferon-gamma (MuIFN-gamma) binds to the extracellular domain of the receptor alpha chain through its N-terminus and subsequently to the cytoplasmic domain of the receptor via its C-terminus. Binding of the C-terminus to the cytoplasmic domain of the receptor is thought to occur following endocytosis of the IFN-gamma-receptor complex. In fact, the MuIFN-gamma C-terminus peptide, MuIFN-gamma (95-133), has full agonist activity on macrophages where it is internalize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
41
0

Year Published

1998
1998
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(44 citation statements)
references
References 15 publications
3
41
0
Order By: Relevance
“…A peptide encompassing residues 95 through 125 of murine IFN-␥, [MuIFN-␥(95-125)], to which the lipophilic moiety was similarly added, was used as a negative control. We have previously shown that MuIFN-␥(95-125) lacked a required nuclear localization sequence for mimetic activity (26). Data presented below demonstrate that mimetics, whether expressed intracellularly or via delivery of chemically synthesized lipopeptides, possessed similar qualitative IFN-␥ mimetic activity.…”
Section: Resultsmentioning
confidence: 73%
See 2 more Smart Citations
“…A peptide encompassing residues 95 through 125 of murine IFN-␥, [MuIFN-␥(95-125)], to which the lipophilic moiety was similarly added, was used as a negative control. We have previously shown that MuIFN-␥(95-125) lacked a required nuclear localization sequence for mimetic activity (26). Data presented below demonstrate that mimetics, whether expressed intracellularly or via delivery of chemically synthesized lipopeptides, possessed similar qualitative IFN-␥ mimetic activity.…”
Section: Resultsmentioning
confidence: 73%
“…Peptides corresponding to residues 95 through 133 and 95 through 125 of murine IFN-␥ were synthesized on an Applied Biosystems 9050 automated peptide synthesizer (Foster City, CA) using conventional fluorenylmethyloxycarbonyl chemistry as described previously (26). The addition of a lipophilic group (palmitoyl-lysine) to the N terminus of the synthetic peptide was performed as the last step by using semiautomated protocol.…”
Section: Cellmentioning
confidence: 99%
See 1 more Smart Citation
“…The peptides used in this study are listed in Table I and were synthesized in our laboratory on an Applied Biosystems 9050 automated peptide synthesizer using conventional fluorenylmethyoxycarbonyl chemistry as described previously (18). A lipophilic (lipo) group (palmitoyl-lysine) was added to the N terminus of peptides to facilitate entry into cells as a last step using a semiautomated protocol.…”
Section: Peptidesmentioning
confidence: 99%
“…DU145 cells were therefore treated with 1-8 mM lipophilic Tkip as shown in Figure 2a, and constitutive phosphorylation of 95 AKFEVNNPQVQRQAFNELIRVVHQLLPESSL 125 a The peptides used in this study were synthesized in our laboratory using conventional fluorenylmethyloxycarbonyl (Fmoc) chemistry as described previously (Szente et al, 1996;Flowers et al, 2004). A lipophilic group (palmitoyl-lysine) was added to the N-terminus of the synthetic peptides during peptide synthesis to enhance cellular uptake (Thiam et al, 1999) STAT3 was determined.…”
mentioning
confidence: 99%